2013
DOI: 10.1111/jar.12031
|View full text |Cite
|
Sign up to set email alerts
|

The Social Information Processing Model as a Framework for Explaining Frequent Aggression in Adults with Mild to Moderate Intellectual Disabilities: A Systematic Review of the Evidence

Abstract: Whilst research relating to the SIP model remains sparse for this population, there was evidence for different patterns of processing between aggressive and non-aggressive individuals. Group diff-erences included interpretation of emotional cues, inter-personal attributions and beliefs about the outcomes of aggressive behaviour. The future direction of SIP research with people who have intellectual disabilities is discussed, along with the possibility of using this framework to help build on current initiative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 40 publications
2
14
0
1
Order By: Relevance
“…Ce TIS est un processus fonctionnel, utilisé en contexte d'interactions sociales, qui favorise l'adaptation sociale. Quelques études ont démontré que les enfants présentant une DI éprouvent des difficultés en résolution de problèmes sociaux, induisant un retard de développement du TIS (Baurain et Nader-Grosbois, 2013;Nader-Grosbois et al, 2013), ou des difficultés plus ciblées à certaines étapes (Larkin, Jahoda et MacMahon, 2013;Van Nieuwenhuijzen, Orobio de Castro, Wijnroks, Vermeer et Matthys, 2009).…”
Section: Introductionunclassified
“…Ce TIS est un processus fonctionnel, utilisé en contexte d'interactions sociales, qui favorise l'adaptation sociale. Quelques études ont démontré que les enfants présentant une DI éprouvent des difficultés en résolution de problèmes sociaux, induisant un retard de développement du TIS (Baurain et Nader-Grosbois, 2013;Nader-Grosbois et al, 2013), ou des difficultés plus ciblées à certaines étapes (Larkin, Jahoda et MacMahon, 2013;Van Nieuwenhuijzen, Orobio de Castro, Wijnroks, Vermeer et Matthys, 2009).…”
Section: Introductionunclassified
“…Students with ASD and those with ID have exhibited nearly equal socio-emotional and executive functioning. Deficits in socio-emotional functioning have been widely documented for children with ASD [50] and at a lesser extent for children with ID [51,52]. Additionally, the authors of [53] reported lower face recognition performances in children with ASD or with Down syndrome than in typically developing children.…”
Section: Similarities and Differences Between Asd And Id Conditionsmentioning
confidence: 99%
“…Reactive aggression may arise either from an increased propensity to behave aggressively, or by a decreased ability to inhibit the expression of aggressive behaviour: so-called 'bottom-up' and 'topdown' mechanisms. This concept is common both to a neurobiological analysis of aggression and to social information-processing models, which have been used to explain social behaviours, including aggression, by outlining the sequence of cognitive processes that occur between encountering and processing social cues, and enacting a response (Crick & Dodge 1996;Larkin et al 2013). There is an extensive literature on the neurobiology of defensive/reactive/impulsive aggression, based on studies in rodent and primate models, and in humans who display irritable or impulsive aggression.…”
Section: Behavioural Processes and Brain Mechanisms In Aggressionmentioning
confidence: 99%